Uji Aktivitas Antibakteri Kombinasi Ekstrak Daun Kelor dan Senggani terhadap Bakteri Escherichia coli dan Staphylococcus aureus secara In Vitro - Putri, Amalia Eka; Andini, Mita Uly; Huda, Choirul (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2022)
Infection is one of the most common diseases today. One of them is an infection caused by Escherichia coli and Staphylococcus aureus bacteria that attack the digestive tract and cause diarrhea. The purpose of this study was to determine the antibacterial activity of Moringa and senggani leaf extracts against Escherichia coli and Staphylococcus aureus bacteria in vitro. By using the disc diffusion method. Moringa and senggani extract ratios of 1:1, 1:2, and 2:1 were used to test the antibacterial activity compared with positive control of chloramphenicol and negative control of DMSO. The results of the inhibition zone obtained in the Escherichia coli bacteria test at a ratio of 1:1 of 11.2 mm, 1:2 of 12 mm, and 2:1 of 11.3 mm. while in the Staphylococcus aureus test the ratio of 1:1 is 10.3 mm, 1:2 is 15.3 mm, and 2:1 is 13 mm. These results indicate that the resulting inhibition zone is in the strong category. It can be said that the combination of KLSG extract has antibacterial activity against Escherichia coli and Staphylococcus aureus.